Alternatives Formation of Bricks Pattern from Trowulan through parametric design - Stephanus Evert Indrawan (IJCAS (International Journal of Creative and Arts Studies), 2018)
This research is a continuation of the potential mapping from Trowulan Art and Crafts commodity based on its material which consist of Terracotta, Stone and Brass. Studies are limited to Terracotta and bricks as its products. Terracotta of Trowulan has a distinctive color texture and the product that based on this material are mostly sculpture, roofs tile, roofs ornament and bricks. Bricks are the most common material for building construction and being exposed in a common principles of bricks formation. This recent research aims to find an alternative principles of bricks formation through parametric design approach. The software that being used are Rhinoceros and Grasshopper plug ins. Product of studies are parametric script that enables designer to make a well calculated simulation and shorten the prototyping process. It is also implemented as design module or designs pattern that can be developed manually by handworkers.